Trajektori Studi Administrasi Publik - Pratama, M. Rizki (Universitas Islam Malang, 2020)
This study explains the trajectory of public administration (PA) time to time. Public Administration has experienced many significant developments since the writing of the study of administrationÂ by Wilson in 1887. Starting from the identity crisis, the re-recognition of the study of public administration to the emergence of new public administration was increasingly growing when the new public management was introduced. The journey of PA has found its own way as a science that must be interpreted as a science that cannot stand alone but has its own character, especially how to look at the affairs of the public sector or everything related to the public in general. PA is not a science that has no clear boundaries or has a high degree of blurring. As long as the criticism shows the dynamics that actually employs PA studies instead of shutting down PA studies themselves. PA experiences patterns from the past to the future can be conceptualized into an PA trajectory. This trajectory certainly cannot be considered full and absolute effect, of course there are several loopholes and really in need to be criticized. The development and change of the PA study has reached an encouraging stage when in the current era the PA study has been considered as a tool to achieve a better society and country life, if the government is considered bad government then the PA is used as a guide to reform as well as being used to review current government performanceÂ through various kinds of PA theories that already exist.